Navigating Religious Discourse in the Digital Era: Social Media as a New Public Sphere - Vera, Nawiroh (Communication, 2026)
Social media has become a new public space enabling religious discourse to occur openly, participatorily, and beyond traditional institutional boundaries. This study aims to analyze how social media function as discursive arenas for discussing religion, as well as how religious practices are transformed through digital mediation. This is a descriptive qualitative study using a case study approach, namely content analysis of YouTube social media the Login program, and the Download program, based on Jürgen Habermas' public sphere theory. Data were obtained through observation of predetermined social media content by observing the dynamics of actors, forms of religious expression, and the epistemological implications of the shift in religious authority in the digital era. The findings indicate that these programs function as digital spaces that facilitate the dissemination of religious knowledge through accessible, engaging, and dialogic formats. The discourse also emphasizes emotional aspects, appreciation, expressions, humor, and jokes. However, the extent to which these platforms fulfill the criteria of an ideal public sphere remains contingent upon depth of critical discussion and the openness to diverse perspectives.